Improving Water Quality Through the Collaboration of BrantaSae, RIVER, and Citizen Science in River Cleaning Actions - Haribowo, Riyanto (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2025)
River pollution in Indonesia represents a significant environmental challenge that tends to escalate alongside the growth of human activities. The engagement of local communities in “citizen science” initiatives facilitated by the BrantaSae platform plays a crucial role in collecting scientific data, particularly in comprehending the extent of ecological harm. Participation in community service activities related to “citizen science” offers a viable approach to rectifying environmental degradation and enhancing public consciousness regarding the significance of ecosystem health. A notable endeavor in this realm involves the cleanup of waste within water sources like rivers and drainage systems, a campaign known as “RIVERlution”. Moreover, the cleaning process entails the categorization of the gathered waste materials. Analysis of the waste items retrieved from the study site reveals a predominance of plastic waste, with LDPE (Low-Density Polyethylene) emerging as the most prevalent polymer type. Thus, the findings underscore the imperative of heightening public awareness and interventions to mitigate waste disposal into water bodies, alongside establishing more effective waste management infrastructures to foster substantial improvements in environmental sustainability and water quality.